2017
DOI: 10.1016/j.jaci.2017.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Reduced need for surgery in severe nasal polyposis with mepolizumab: Randomized trial

Abstract: In patients with recurrent nasal polyposis receiving topical corticosteroids who required surgery, mepolizumab treatment led to a greater reduction in the need for surgery and a greater improvement in symptoms than placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
452
5
15

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 441 publications
(482 citation statements)
references
References 32 publications
10
452
5
15
Order By: Relevance
“…However, the subgroup analysis in this study showed that no difference for baseline TPSs and local IL-5 levels was found. Similarly, in the Bachert et al (23) study, mepolizumab caused a significant improvement in the treatment group as compared to control group from week 9 to week 25.…”
Section: Literature Searchmentioning
confidence: 64%
See 4 more Smart Citations
“…However, the subgroup analysis in this study showed that no difference for baseline TPSs and local IL-5 levels was found. Similarly, in the Bachert et al (23) study, mepolizumab caused a significant improvement in the treatment group as compared to control group from week 9 to week 25.…”
Section: Literature Searchmentioning
confidence: 64%
“…On the contrary, the mean difference between mepolizumab and control group in PNIF values was statisticallly significant (p=0,027, in the second mepolizumab study (23) . At last, Bachert et al (22) reported a statistically significant mean difference in PNIF for dupilumab group vs placebo (p=0,002).…”
Section: Nasal Airflow (Pnif) and Olfaction (Upsit)mentioning
confidence: 79%
See 3 more Smart Citations